Nefroprotective properties of febuxostat in chronic renal failure - Babenko, Z. V. (Journal of Education, Health and Sport, 2019)
Urgency. Chronic renal failure poses medical, social and organizational problem because of high mortality, disability and complexity of modern treating methods technical support. The objective: to evaluate the effectiveness of febuxostat in controlling hyperuricemia in patients with end-stage chronic renal failure. Material and methods. 90 patients were divided into three groups in accordance with the use of febuxostat at a dose of 40 mg to reduce uric acid level: group 1 (n=30) - terminal chronic renal failure patients who are not yet receiving renal replacement therapy; Group 2 (n=30) peritoneal dialysis patients; 3 group (n=30)- hemodialysis patients. Results and discussion. Febuxostat use led to uric acid level decrease in all groups under study, increase of the functional renal reserve level in the 1st and 2nd groups. In the 3rd group patients (hemodialysis patients), only uric acid level changes were studied in connection with the absence of in this cohort residual functional renal reserve. The use of febuxostat determines, with decrease in uric acid levels, increase in the residual functional renal reserve and improvement the patients’ quality of life according to the questionnaire data. These results are best reflected in pre-dialysis patients with terminal chronic renal failure. Conclusion: treatment with febuxostat leads to a marked decrease in the level of serum uric acid, increase of residual functional renal reserve and improvement of chronic renal failure patients quality of life, which indicates its good nephroprotective properties.